2016
DOI: 10.1155/2016/1847325
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Carbon Nanoreinforced Epoxy Composites

Abstract: The present study attempts to investigate the influence of multiwalled carbon nanotubes (MWCNTs) and graphite nanoplatelets (GNPs) on thermal conductivity (TC) of nanoreinforced polymers and nanomodified carbon fiber epoxy composites (CFRPs). Loading levels from 1 to 3% wt. of MWCNTs and from 1 to 15% wt. of GNPs were used. The results indicate that TC of nanofilled epoxy composites increased with the increase of GNP content. Quantitatively, 176% and 48% increase of TC were achieved in nanoreinforced polymers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 19 publications
3
32
0
Order By: Relevance
“…To overcome this, in the past years polyethylene nanocomposites with several inorganic nanofilllers, such as nanoparticles, clays, graphene and carbon nanotubes (CNTs) have been prepared and studied [1][2][3][4][5][6][7][8][9][10]. CNTs have attracted attention because of their structure and properties [11,12]. HDPE reinforced with CNTs and nano-diamonds was studied in [13].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this, in the past years polyethylene nanocomposites with several inorganic nanofilllers, such as nanoparticles, clays, graphene and carbon nanotubes (CNTs) have been prepared and studied [1][2][3][4][5][6][7][8][9][10]. CNTs have attracted attention because of their structure and properties [11,12]. HDPE reinforced with CNTs and nano-diamonds was studied in [13].…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al [20] found that the thermal conductivity of GNP coated fibre laminates was 13% higher with the addition of 1 wt.% GNP. Kostagiannakopoulou et al [21] indicated that a 176% and 48% increase in thermal conductivity was achieved in nanomodified polymers and CFRPs, respectively, with the addition of 15 wt.% GNP into the epoxy matrix. Nevertheless, most of the GNP doped epoxy resins exhibit an increased viscosity which inhibits subsequent composite manufacturing processes like resin transfer moulding or vacuum infusion.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticle reinforced polymers, synergistically combine the properties of both the host polymer matrix and the discrete nanoparticles . Epoxy nanocomposites exhibit a wide range of positive characteristics, such as dielectric behaviors, thermal stability properties, good corrosion resistance, mechanical performance, and excellent tribological properties . For example, layered nanosilica particles have been introduced into epoxy resin to improve both toughness and mechanical strength .…”
Section: Introductionmentioning
confidence: 99%